Pengaruh Jumlah Anggota dan Volume Usaha Pada Koperasi Simpan Pinjam di Kecamatan Buleleng - Emi Indarwati; Wayang Cipta (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study aims to examine the effect of the total of members and business volume on result of operation (SHU) simultaneously or partially. The research design used quantitative causal. The research subjects are Savings and Loans Cooperatives in Buleleng District which are registered with the Buleleng Regency Trade, Industry and UKM Cooperatives Office, and the objects research are the total of members, business volume, and SHU. The sampling technique used was purposive sampling is sample many of 15 cooperation. Data were collected by documents recording, it’s analyzed by multiple linear regression analysis. The results showed that (1) the total of members and business volume had a significant effect on SHU, (2) the total of members had a positive and significant effect on SHU, (3) business volume had a positive and significant effect on SHU.